Addressing the Criticalities for the Deployment of Adsorption-based CO2 Capture Processes. (July 2017) - Zanco, Stefano Edoardo; Joss, Lisa; Hefti, Max; Gazzani, Matteo; Mazzotti, Marco
Abstract: Adsorption-based separations are a promising alternative for CO2 capture, for both pre-combustion and post-combustion applications. The desirable characteristics of solid sorbents and the flexible cyclic nature of the processes operated with fixed beds open the doors for potential improvement over the most established technology, which is represented by amine-scrubbing systems. Two main routes are available for the regeneration of the sorbents, i.e. either pressure-driven (PSA/VSA cycles) or temperature-driven desorption (TSA cycles) respectively. A series of criticalities are encountered in the implementation of both solutions: They prevent adsorption-based separations to reach breakthrough performances, in terms of energy consumption and plant productivity. To tackle these issues, research should address different aspects: Besides the development of innovative sorbents, the fine-tuning of both unit operation and cycle design is believed to be the key to advancing this technology towards commercial success.